The contribution of asymptomatic Plasmodium infections to the transmission of malaria in Kayin state, Myanmar - Chaumeau, V; Kajeechiwa, L; Fustec, B; Landier, J; Naw Nyo, S; Nay Hsel, S; Phatharakokordbun, P; Kittiphanakun, P; Nosten, S; Thwin, MM; Win Tun, S; Wiladphaingern, J; et al. (Oxford University Press (OUP), 2018)
BACKGROUND: The objective of mass antimalarial drug administration (MDA) is to eliminate malaria rapidly by eliminating the asymptomatic malaria parasite reservoirs and interrupting transmission. In the Greater Mekong Subregion, where artemisinin-resistant Plasmodium falciparum is now widespread, MDA has been proposed as an elimination accelerator, but the contribution of asymptomatic infections to malaria transmission has been questioned. The impact of MDA on entomological indices has not been characterized previously. METHODS: MDA was conducted in 4 villages in Kayin State (Myanmar). Malaria mosquito vectors were captured 3 months before, during, and 3 months after MDA, and their Plasmodium infections were detected by polymerase chain reaction (PCR) analysis. The relationship between the entomological inoculation rate, the malaria prevalence in humans determined by ultrasensitive PCR, and MDA was characterized by generalized estimating equation regression. RESULTS: Asymptomatic P. falciparum and Plasmodium vivax infections were cleared by MDA. The P. vivax entomological inoculation rate was reduced by 12.5-fold (95% confidence interval [CI], 1.6-100-fold), but the reservoir of asymptomatic P. vivax infections was reconstituted within 3 months, presumably because of relapses. This was coincident with a 5.3-fold (95% CI, 4.8-6.0-fold) increase in the vector infection rate. CONCLUSION: Asymptomatic infections are a major source of malaria transmission in Southeast Asia.